STRATEGI MARKETING SYARIAH DALAM UPAYA MENINGKATKAN OMZET PENJUALAN - Wuni Sapoan, A’is Mulie; Mustofa, Mustofa; Imani, Safarinda; Zainuddin, Faiz (Al-Idarah, 2025)
Marketing strategy is a process that plays an important role for companies that market goods and services to consumers because every company has the same opportunities in doing business, so there can be competition between companies and similar competitors in capturing the market. In this era of globalization, economic development is very fast, business competition is very tight, this applies to all business fields. Like UD. Friends of Tani who are engaged in agricultural business. Weaknesses and advantages of business entities should be analyzed so that they become a strong starting point for business entities in making effective and efficient decisions and to strengthen their position from existing competitors. UD. Sahabat Tani has made efforts to improve its business marketing by utilizing social media networks and word of mouth with the aim that the company can increase its sales turnover graph and be able to compete in competition in the digital era as well as form awareness of its surviving business which is worthy of being a partner in investing.